MOTIVASI DAN BIMBINGAN BAGI PENYANDANG DISABILITAS SENSORIK DI KOTA PALEMBANG - Wagisri, Wagisri; Mahriadi, Nopriawan; Havivi, Siti Lady; Anita, Sumarni Bayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Social work helps individuals, groups/communities and society to overcome their problems and carry out their social functions. One of the Tri Dharmas of Higher Education is Community Service, in carrying out this service it is hoped that you will be able to contribute to society by paying attention to the needs of the community itself. This service is supported by the Social Welfare Study Program which invites STISIPOL Candradimuka students to be sensitive to environmental conditions, be able to collaborate between students and the community and be able to apply the theories they have learned in society. Service methods include Focus Group Discussion, Motivation, and Skills Guidance which is carried out for 25 days. Social welfare services include Religious Social Mental Guidance Activities, Massage Guidance, Music Arts Skills Guidance, Braille Computer Guidance, Culinary Skills Guidance and Sports Activities. In general, the service activities carried out at UPTD PSRD-Sensorik for approximately 1 month can be carried out well.